2017
DOI: 10.1186/s13018-017-0698-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for predicting increased surgical drain output in patients after anterior cervical corpectomy and fusion

Abstract: BackgroundAlthough measures to reduce and treat the postoperative surgical drain output are discussed, along with the increased interest in causative factors related to the prevention and treatment reported by many studies, these are still controversial.MethodsA retrospective study was conducted on a consecutive series of 217 patients who had underwent ACCF between January 2016 and March 2017. Patients were categorized based on normal or increased total drain output. These two groups were compared for demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The confidence interval of the weighted mean difference (WMD) was wide and the possibility that the real WMD favors largely the group of drill guide template. We think that there are two factors contributing to the above results: the limited number of studies that we included and less intraoperative blood loss in the cervical surgery [33,34]. This study illustrated the advantages of the drill guide template, which can accurately and effectively increase the accuracy rate of pedicle screw placement and decrease the risk of postoperative complications, such as shorten the operative time and reduce intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 79%
“…The confidence interval of the weighted mean difference (WMD) was wide and the possibility that the real WMD favors largely the group of drill guide template. We think that there are two factors contributing to the above results: the limited number of studies that we included and less intraoperative blood loss in the cervical surgery [33,34]. This study illustrated the advantages of the drill guide template, which can accurately and effectively increase the accuracy rate of pedicle screw placement and decrease the risk of postoperative complications, such as shorten the operative time and reduce intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 79%
“…Although no other studies have reported risk factors for increased drain output following type I thyroplasty, our findings corroborate evidence from several other surgical procedures. In two separate studies on patients undergoing anterior cervical discectomy, history of smoking and older age were both found to predict higher surgical drain output postoperatively 11,12 . History of smoking has been associated with an increased risk of bleeding following other head and neck surgeries, including thyroidectomies 13 and tonsillectomies 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common reason spine surgeons place a drain following anterior cervical surgery is the prevention of wound hematoma due to the feared consequence of airway compromise [4,20,21]. This complication occurs in roughly 0.20% of patients undergoing anterior cervical surgery [22,23].…”
Section: Why Most Surgeons Consider Placing a Drainmentioning
confidence: 99%
“…If not recognized expeditiously, airway compromise can progress quickly increasing morbidity and mortality. Thus, some surgeons believe it is important to know which factors are associated with increased drain output to guide patient selection on drain placement [20,21].…”
Section: Why Most Surgeons Consider Placing a Drainmentioning
confidence: 99%